2005
DOI: 10.1038/sj.embor.7400418
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch repair participates in error‐free processing of DNA interstrand crosslinks in human cells

Abstract: DNA interstrand crosslinks (ICLs) present formidable blocks to DNA metabolic processes and must be repaired for cell survival. ICLs are induced in DNA by intercalating compounds such as the widely used therapeutic agent psoralen. In bacteria, both nucleotide excision repair (NER) and homologous recombination are required for the repair of ICLs. The processing of ICLs in mammalian cells is not clearly understood. However, it is known that processing can occur by NER, which for psoralen ICLs can be an error-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(137 citation statements)
references
References 32 publications
6
130
1
Order By: Relevance
“…Thus, this application has the potential to directly inactivate genes, rather than transiently regulating gene expression. As an example, triplex formation can be used to direct site-specific DNA damage and thereby induce DNA repair synthesis locally, independent of replication synthesis [30][31][32]. We have used TFOs targeted to the c-MYC gene to stimulate repair synthesis in the presence of an antitumor antimetabolite, gemcitabine, to increase its incorporation into DNA.…”
Section: Directing Site-specific Dna Damagementioning
confidence: 99%
“…Thus, this application has the potential to directly inactivate genes, rather than transiently regulating gene expression. As an example, triplex formation can be used to direct site-specific DNA damage and thereby induce DNA repair synthesis locally, independent of replication synthesis [30][31][32]. We have used TFOs targeted to the c-MYC gene to stimulate repair synthesis in the presence of an antitumor antimetabolite, gemcitabine, to increase its incorporation into DNA.…”
Section: Directing Site-specific Dna Damagementioning
confidence: 99%
“…A clear role for ERCC1-XPF in the uncoupling step has been established both in vitro and in vivo [20,21,25,[28][29][30][31], however, it is unlikely that this complex can carry out this step without the assistance of additional factors. We previously showed a requirement for the mismatch repair factor MutSβ in the early stage of ICL processing using an in vitro assay termed CRS (for cross-link induced repair synthesis) [21], and several other reports have demonstrated a role for mismatch repair components in ICL removal in vivo [26,27,32,33]. In addition, MSH2 and ERCC1-XPF have been shown to interact by co-IP experiments [26].…”
Section: Discussionmentioning
confidence: 95%
“…Recently, we and others have shown that components of the mismatch repair pathway play an important role in the processing of DNA ICLs [21,26,27]. We, therefore, examined several mismatch repair-deficient cell lines in our HDR assay.…”
Section: Role Of Mismatch Repair Proteins In Icl-mediated Stimulationmentioning
confidence: 99%
“…There are four well known DNA repair pathways which are responsible for repairing various of DNA damage, including base excision repair (BER), nucleotide excision repair (NER), double-strand break repair (SSBR) and homologous recombination repair (HRR). Nucleotide excision repair (NER) pathway is an important mechanism that maintains genomic integrity by removing DNA bulky lesions or interstrand adducts induced by exogenous and/ or endogenous factors (Neumann et al, 2005;Wu et al, Bo Yang 1 *, Wei-hua Chen 2 , Xiao-fei Wen 2 , Hui Liu 1 , Feng Liu 1 2005). The variation of DNA repair genes in the NER pathway may affect the capacity of encoded DNA repair enzymes, and subsequently enhance the risk of cancer (Goode et al, 2002;Hu et al, 2002;Hu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%